Measuring the Success of Counter-Trafficking Interventions in the Criminal Justice Sector: Who decides—and how? - Anne Gallagher; Rebecca Surtees (Anti-Trafficking Review, 2012)
Global concern about human trafficking has prompted substantial investment in counter-trafficking interventions. That investment, and the human rights imperatives that underpin counter-trafficking work, demand that interventions demonstrate accountability, results and beneficial impact. How this can happen in practice is complicated and contested. This article, which considers success measurements with respect to criminal justice interventions, seeks to cut through the complexities presented by multiple theories and elaborate methodologies by focusing on one key issue: who decides success, and how? A review of evaluation reports and interviews with practitioners confirm that determinations of success (or failure) will vary according to: (i) who one consults and their role in the intervention; (ii) the criteria against which success is measured; and (iii) the assumptions that are built into that criteria. Each aspect is considered with reference to examples and insights drawn from recent practice. A major finding of the article is that the lack of an overarching vision of what “success” might look like allows mediocre or even harmful interventions to flourish and good work to go unrecognised and unrewarded.